IMPROVING READING COMPREHENSION WITH THE USE OF AUTHENTIC MATERIALS IN TEACHING PROCESS - Eshpulatova, Ugiloy (Журнал иностранных языков и лингвистики, 2023)
The idea of using authentic material in language teaching is supported among references and many professionals in the field of language pedagogy. Authentic material provides the learners with many significant advantages and promotes them with high motivation and interest in language learning and lead to improving communicative competence. This article attempted to investigate EFL teachers’ attitudes and beliefs regarding the use of authentic materials at high school level according to communicative language principles, focusing on reading skill.